An Alternative Laboratory Information System (LIS) in Primary and Secondary Laboratories - Cabuyao, Christian Josef; Labinghisa, Nichole Anne; Quendangan, Cyril Mae; Sarte, Miguel; Vargas, Jullia Klarisse; Vergara, Jezrele Gem; Wong Hin, Jasper Franz (International Journal of Arts, Sciences and Education, 2021)
A Laboratory Information System (LIS) helps in laboratory workflow by providing an ease of access for the patient’s data that reduces the overall turnaround time (TAT). The study was designed specifically to aid in the pre- and post-analytical phases. The rationale behind this study is to develop an alternative LIS that is functional and affordable that can be used in laboratory workflow. A survey was conducted to determine the preference of the respondents on LIS operations in terms of Functionality, Interface, Patient Records, Results and Reports viewing, and Additional Features. Data from the said survey were collated and used as the basis for the necessary functionalities of the RbP LIS developed. The RbP LIS was pilot tested at two freestanding private laboratories to determine its significant difference on turnaround time versus the traditional paper-based method. A researcher-made 5-point Likert Scale survey was used as an assessment tool to gather the insights of respondents with regards to their experience in using the RbP LIS vs traditional paper-based method in terms of accuracy, ease of accessioning, and ease of archiving. These variables served as the basis of data necessary for the analysis and interpretation of data. The parameters aforementioned above were measured in the study. Decreased turnaround times and accession errors with better accuracy in effective data inputting which allows for easier corrections of errors are noted based on the respondents’ inputs. The pilot testing of the proposed LIS implied that there is a significant difference between the traditional paper-based method of accessioning and the RbP LIS itself which resulted in the respondents favoring the proposed RbP LIS over paper-based methods of data accessioning.